2017
DOI: 10.1111/1755-6724.13068
|View full text |Cite
|
Sign up to set email alerts
|

Biomediated Precipitation of Calcium Carbonate in a Slightly Acidic Hot Spring, Yunnan Province

Abstract: A slightly acidic hot spring named “Female Tower” (t=73.5°C, pH=6.64) is located in the Jifei Geothermal Field, Yunnan Province, southwestern China. The precipitates in the hot spring are composed of large amounts of calcite, aragonite and sulfur. Scanning electron microscopy (SEM) analyses reveal that the microbial mats were formed from various coccoid or rod‐shaped filamentous microbes. Transmission electron microscopy (TEM) shows that the intracellular sulfur granules are commonly associated with these micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Figure 5E is a SEM micrograph of the 10 h product (with EDS results) performed after extraction with 20 g L −1 citric acid solution. The dotted circle in the centre of Figure 5A (1 h product) highlights pointedlike acicular crystalline structures (Tang et al 2009;Jiang et al 2017), probably referring to CaCO3 in the crystalline form of aragonite. Some small rhombohedral crystals characteristic of calcite CaCO3 (indicated by an arrow) (Rautaray et al 2003;Chien et al 2006;Kim et al 2017) appear in the lower right corner of Figure 5A.…”
Section: Sem-eds Characterisationmentioning
confidence: 98%
“…Figure 5E is a SEM micrograph of the 10 h product (with EDS results) performed after extraction with 20 g L −1 citric acid solution. The dotted circle in the centre of Figure 5A (1 h product) highlights pointedlike acicular crystalline structures (Tang et al 2009;Jiang et al 2017), probably referring to CaCO3 in the crystalline form of aragonite. Some small rhombohedral crystals characteristic of calcite CaCO3 (indicated by an arrow) (Rautaray et al 2003;Chien et al 2006;Kim et al 2017) appear in the lower right corner of Figure 5A.…”
Section: Sem-eds Characterisationmentioning
confidence: 98%
“…Specifically, the positive δ 13 C values for calcite cements suggest that carbon sources are derivation of dissolved carbon from sea water (−4‰-4‰) (Bath et al, 1987), dissolved carbon from lacustrine water (2.9‰-9.3‰) (Cao et al, 2007;Lyu et al, 2018;Tian et al, 2018) or microbial fermentation of organic matter (8‰-23‰) (Macaulay et al, 2000;Head et al, 2003). While, the negative δ 13 C values for the calcite cements indicate that carbon sources include meteoric water influence (−7‰-−3.5‰) (Schmid et al, 2004), magmatic influence (−8‰-−4‰) (Hoefs, 1973;Xi et al, 2016;Zhu et al, 2017), decarboxylation of organic matter (−10‰-−25‰) (Irwin et al, 1977), bacterial oxidation (−13‰-−25‰) (Irwin et al, 1977;Bath et al, 1987), bacterial sulphate reduction (−30‰-−25‰) (Irwin et al, 1977;Suess and Whiticar, 1989;Jiang et al, 2017), hydrothermal induced methanogenesis oxidation (−36‰-−27‰) (Bristow et al, 2011;Bian et al, 2013) and biogenic induced methanogenesis oxidation (−66‰ -−35‰) (Suess and Whiticar, 1989;Bristow et al, 2011).…”
Section: Carbon Sources Of Carbonate Cementsmentioning
confidence: 99%
“…Aquificae, isolated from hot springs in Yunnan province, China were found to be associated with CaCO3 precipitation[53]. Dhami et al[50] reported a strain of Bacillus megaterium, isolated from…”
mentioning
confidence: 99%